Bone Disease: The Integration of Nano- and Macro-Scale Studies - Arnold, Emily (Cranfield University, 2020)
Bone is a hierarchical structure that provides support and protection to a body. In the macro-structure of bone, geometry affects it ability to perform these functions, while in the micro-structure the material properties dictate changes. The easy substitution of atoms into the crystal, as well as the binding of extraneous proteins to the surface, have been found to alter many material properties.This research aims to develop a greater understanding of the fundamental properties and behaviours of the mineral component of bone (biological Hydroxyapatite or HA) through several techniques, some that are well documented within the field of research and some that are not. While X-Ray Diffraction (XRD) and Fourier Transform Infrared Spectroscopy (FTIR) are often used in the study of HAp, this research aims to expand the lesser-used methods used to include X-Ray PDF Studies with the use of Synchrotron Radiation, as well as Differential Scanning Calorimetry (DSC), and Thermogravimetric Analysis (TGA).By building a cohesive model one step at a time we can begin to understand fundamental material characteristics of this fascinating building block of life.
Keywords: 'Bone'; 'Osteoporosis'; 'Hydroxyapatite'; 'DSDS19'; 'DSDS19 3MT'; 'Biomechanics'